Comparative Legal Analysis of the Death Penalty Law - Alfia Hani, Zarda; Thalib, Hambali; Sutiawati, Sutiawati (Faculty of Law, Universitas Muslim Indonesia, 2025)
This research aims to analyze the regulation of criminal offenses punishable by the death penalty and compare the formulation of the death penalty between the Penal Code under Law Number 1 of 1946 (Dutch Colonial Penal Code) and Law Number 1 of 2023 concerning the Penal Code (National Penal Code). This study employs a normative legal research method with a statutory approach and a case approach. Legal data were collected through literature studies and analyzed qualitatively. The findings of this research indicate that the regulation of criminal offenses punishable by the death penalty in Indonesia is found in the Penal Code, the Narcotics Law, the Human Rights Law, the Corruption Crime Law, the Human Rights Court Law, and the Law on the Misuse of Firearms and Explosives. Furthermore, a comparison of the death penalty between the Dutch Colonial Penal Code and the National Penal Code of 2023 reveals a shift from the death penalty as a principal punishment to a death sentence with a probationary period and an alternative life imprisonment sentence. The comparison also includes differences in the legal basis, the formulation of the death penalty, the criteria for its application, and the procedures for its execution. This research recommends further studies on severe crimes that have not been explicitly regulated for the application of the death penalty.